Jewish Messiahs in a Christian Empire : A History of the Book of Zerubbabel - Himmelfarb, Martha (Cambridge, MA : Harvard University Press, 2017)
The seventh-century CE Hebrew work Sefer Zerubbabel (Book of Zerubbabel) a tale of two messiahs is the first full-fledged messianic narrative in Jewish literature. Martha Himmelfarb offers a comprehensive analysis of this rich understudied text, illuminating its distinctive literary features and the complex milieu from which it arose.
Frontmatter -- Contents -- Introduction -- 1. Text and Context -- 2. The Mother of the Messiah -- 3. The Messiah Son of David and the Suffering Servant -- 4. The Servant-Messiah beyond Sefer Zerubbabel -- 5. The Dying Messiah Son of Joseph -- 6. Sefer Zerubbabel after Islam -- Conclusion -- Appendix. Translation of Sefer Zerubbabel according to the Sefer Hazikhronot Manuscript -- Notes -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: Apocalyptic literature -- History and criticism; Christianity -- Influence; Eschatology, Jewish; Messiah -- Judaism